Effect of immersion in distilled water or phosphate-buffered saline on the solubility, volumetric change and presence of voids within new calcium silicate-based root canal sealers - Torres, F. F.E. [UNESP]; Zordan-Bronzel, C. L. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Chávez-Andrade, G. M. [UNESP]; Pinto, J. C. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley, 2020)
Aim: To assess the effect of immersion in distilled water or phosphate-buffered saline (PBS) on the solubility, volumetric change and presence of voids of calcium silicate-based root canal sealers (TotalFill BC, Sealer Plus BC and Bio-C), in comparison with the gold standard epoxy resin-based sealer (AH Plus). Methodology: All properties were evaluated after immersion in distilled water or PBS. Solubility was determined by the percentage of mass loss, whereas volumetric change and presence of voids were evaluated by micro-computed tomography, after 7 days of immersion. The volumetric change and percentage of voids between the baseline (after setting) and the experimental period were calculated. Statistical analysis was performed using one-way anova and Tukey's or Student's t-tests (α = 0.05). Results: The calcium silicate-based sealers had significantly greater solubility and volumetric loss than AH Plus, after immersion in distilled water or PBS (P < 0.05). Bio-C had the greatest solubility (P < 0.05), followed by TotalFill BC and Sealer Plus BC, which were similar (P > 0.05). Regarding the volumetric change, AH Plus had a volume increase, with similar values in distilled water and PBS (P > 0.05). TotalFill BC, Sealer Plus BC and Bio-C had a similar volumetric change (P > 0.05). The calcium silicate-based materials had the greatest solubility and volume loss after immersion in distilled water (P < 0.05). There was no difference in the percentage of voids amongst the sealers, before and after immersion in distilled water or PBS (P > 0.05). Conclusions: TotalFill BC, Sealer Plus BC and Bio-C had significantly greater solubility and volumetric loss than AH Plus. Although storage in PBS significantly reduced the solubility and volumetric change of calcium silicate-based sealers, their solubility remained above that recommend by ISO 6876. All the sealers evaluated had low and similar voids, even after immersion in distilled water or PBS.
Keywords: calcium silicate; endodontics; micro-CT; physicochemical properties; root canal filling material